2007
DOI: 10.1007/s11745-007-3098-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence of Docosahexaenoic Acid from Different Algal Oils in Capsules and in a DHA‐Fortified Food

Abstract: Docosahexaenoic acid (DHA), a long-chain omega-3 fatty acid, is important for eye and brain development and ongoing visual, cognitive, and cardiovascular health. Unlike fish-sourced oils, the bioavailability of DHA from vegetarian-sourced (algal) oils has not been formally assessed. We assessed bioequivalence of DHA oils in capsules from two different algal strains versus bioavailability from an algal-DHA-fortified food. Our 28-day randomized, placebo-controlled, parallel group study compared bioavailability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 48 publications
1
70
0
Order By: Relevance
“…Both DHA oils are used in food and dietary supplements [30] and are Generally Recognized as Safe (GRAS) for food. DHA-T oil in combination with ARASCO oil, an oil rich in ARA, is GRAS for the fortification of infant formula.…”
Section: Animals and Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both DHA oils are used in food and dietary supplements [30] and are Generally Recognized as Safe (GRAS) for food. DHA-T oil in combination with ARASCO oil, an oil rich in ARA, is GRAS for the fortification of infant formula.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…DHA-T oil in combination with ARASCO oil, an oil rich in ARA, is GRAS for the fortification of infant formula. DHA-S oil has been used in a number of clinical studies [31][32][33], as has the DHA-T oil [30,34]. LC-PUFA are present as triglycerides within these oils.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Additional studies are needed to better assess both benefits and risks of fish oil supplements. A useful approach may be to apply LCPUFA produced by certain species of marine algae that can be cultured industrially to provide the "fish" oil (Wen and Chen, 2003) as a promising alternative and contaminant-free source (Arterburn et al 2007). However, plasma LCPUFA concentrations after fish or fish oil capsule intakes showed that LCPUFA from fish were more effectively incorporated into plasma lipids than when administered as capsules (Visioli et al 2003).…”
Section: Cardiovascular Outcomes-althoughmentioning
confidence: 99%
“…Omega-3 fatty acids have been found in algeal sources which are equivalent to the DHA levels found in fresh fish. (Arterburn et al, 2007;Arterburn, 2008) Indeed these algeal supplements containing DHA have been found to raise the plasma erythrocyte omega-3 fatty acid levels. (Otto, 2000) More recently Hawthorne et al, (2007) revealed that supplementation of this form of DHA in orange juice significantly improved the plasma phospholipid levels in children.…”
Section: Omega-3 Fatty Acids (Docosahexaenoic Acid-dha)mentioning
confidence: 99%